Data from: Nutrients influence the thermal ecophysiology of an intertidal macroalga: multiple stressors or multiple drivers? - Colvard, Nicholas; Helmuth, Brian (2016)
Urbanization of coastlines is leading to increased introduction of nutrients from the terrestrial environment to nearshore habitats. While such nutrient influxes can be detrimental to coastal marine organisms due to increased eutrophication and subsequent reduced oxygen, they could also have positive effects (i.e., increased food availability) on species that are nitrogen-limited such as macroalgae. Nutrient enrichment in this environment thus has the potential to counteract some of the negative impacts of increasing temperatures, at least for some species. Characterizing the physiological response of organisms to simultaneous changes in multiple drivers such as these is an important first step in predicting how global climate change may lead to ecological responses at more local levels. We evaluated how nutrient enrichment (i.e., nitrogen availability) affected the growth of Fucus vesiculosus, a foundational macroalgal species in the North Atlantic rocky intertidal zone, and found that nutrient-enriched algal blades showed a significant increase in tissue growth compared to individuals grown under ambient conditions. We further quantified net photosynthesis by ambient and nutrient-enriched tissues at saturating irradiance over a range of temperature conditions (5°-30°C). Respiration was unaffected by nutrient treatment; however, there was a significant increase in photosynthetic oxygen production for nutrient-enriched tissue compared to ambient, but only at elevated (≥18°C) temperatures. This study contributes to a growing body of literature showing the complexity of responses to changes in multiple drivers, and highlights the importance of studying the impacts of global climate change within the context of more local environmental conditions.